Algorithms and Data Structures 11th International Symposium, WADS 2009, Banff, Canada, August 21-23, 2009. Proceedings - Dehne, Frank; Sack, Jörg-Rüdiger; Toth, Csaba D. (Theoretical Computer Science and General Issues, 2009)
This book constitutes the refereed proceedings of the 11th Algorithms and Data Structures Symposium, WADS 2009, held in Banff, Canada, in August 2009. The Algorithms and Data Structures Symposium - WADS (formerly "Workshop on Algorithms and Data Structures") is intended as a forum for researchers in the area of design and analysis of algorithms and data structures. The 49 revised full papers presented in this volume were carefully reviewed and selected from 126 submissions. The papers present original research on algorithms and data structures in all areas, including bioinformatics, combinatorics, computational geometry, databases, graphics, and parallel and distributed computing.